Analisis Penerapan Pajak E-Commerce Sebagai Upaya Ekstensifikasi Pajak Guna Meningkatkan Pendapatan Negara - Nurul Mahmudah; Risnaningsih Risnaningsih; Hari Purnomo (Ecobuss, 2023)
ABSTRACT This research was created with purpose to decipher more intensively about the study of e-commerce tax. The extension of tax scope in commercial sector including e-commerce was implemented for increasing revenue of the states. This study become important topic to discuss based on the fact of majority of people are inseparable from internet for doing daily activities including finished goods and services transaction. Because of that rapid development can be a chance to increase state revenue from tax imposition and management to that sector. For methods which applied in this research will use qualitative and descriptive approach. Qualitative menas the researcher will observe the object that become the main focus of the research directly. After that the result of observation will be described in some sentences that already arranged in a such way for explaining and discuss the research object more clearly. Next for gathering the data, researchers use both of type data consist of primary and secondary data. For primary, researcher obtained by interviewing some source persons. Meanwhile for secondary data, researchers gather them from any kind of competent books. Then from the processing and explaining of gathered data will enter to the analyzing stage. This analyzing activty involve some aspects for example : calculating the estimation of tax quantity that can be obtained by state from e-commerce and study furthermore about any kind of facts from primary and secondary data for doing mix and match become whole explaination. From those systematics analysis, researchers able to get into conclusion. In general, this research shows that tax imposition for e-commerce sector as an effort to increase state revenues can be held by 3 phases, they are : preparation phase, execution phase, and evaluation phase. Beside that for maintaining the management of e-commerce tax thus Directorate General of Taxation as the tax management authorized institution needs to w cooperate with the Center for Financial Transaction Reporting and Analysis (PPATK) and the Ministry of Communications and Information Technology. Keywords: e-commerce, extensification tax state revenue